Characterisation of particles within and aerosols produced by nano-containing consumer spray products. (December 2020) - Laycock, Adam; Wright, Matthew D.; Römer, Isabella; Buckley, Alison; Smith, Rachel
Abstract: Nanoparticles have been incorporated into a range of consumer spray products, providing the potential for inadvertent inhalation by users and bystanders. The levels and characteristics of nanoparticle inhalation exposures arising from the use of such products are important inputs to risk assessments and informing dose regimes for in vitro and in vivo studies investigating hazard potentials. To date, only a small number of studies have been undertaken to explore both the aerosols generated from such products and the metal nanoparticles within them. The objective of the current study was to add to the limited data in this field by investigating a range of nano-containing spray products available within the UK. Six products were selected and the nanoparticles characterised using a combination of techniques, including: inductively coupled plasma mass spectrometry (ICP-MS), dynamic light scattering (DLS), nanoparticle tracking analysis (NTA), transmission electron microscopy energy-dispersive X-ray spectroscopy (TEM-EDX) and single particle ICP-MS (spICP-MS). The aerosol produced by these products, when sprayed within a glovebox, was characterised by scanning mobility particle sizer (SMPS) and an aerodynamic particle sizer (APS). A cascade impactor with thirteen stages (NanoMOUDI) was used with one product to generate information on the size specific nanoparticle elemental distribution within the aerosol. The results demonstrated the presence of solid nanoparticles (silver, gold or silica) in each of the products at low concentrations (<13 ppm). TEM and (sp)ICP-MS provided reliable information on nanoparticle size, shape, number and mass, while the light scattering methods were less effective due to the complex matrices of the products and their lack of chemical specificity. The aerosols varied significantly across products, with particle and mass concentrations spanning 5 orders of magnitude (10 - 10 6 cm −3 and 0.3–7600 μg m −3, respectively). The NanoMOUDI results clearly indicated non-uniform distribution of silver within different aerosol particle size ranges. Graphical abstract: Image 1 Highlights: Nanomaterials (Ag, Au, silica) characterised in 6 consumer spray products. Multi-method analytical approach allowed characterisation of particles and aerosols. Large variations in aerosol mass and number concentrations across the products. Non-uniform distribution of nanoparticles across aerosol particle size distribution.